The impact of upgrading administrative rank on regional innovation from an agglomeration perspective: a quasi-natural experiment based on the establishment of Chongqing as a province-level municipality - Wei, Ling; Zeng, Bing (Frontiers in Political Science, 2025)
IntroductionAdministrative rank, as an intuitive manifestation of a region’s political capital, significantly influences regional agglomeration capacity and innovative development.MethodsThis study utilizes Chongqing’s promotion to a province-level municipality as a quasi-natural experiment, employing panel data from 219 counties in Sichuan and Chongqing (1992–2010) and applying the difference-in-differences (DID) method to evaluate the impact of administrative rank upgrades on regional innovation.ResultsThe findings show: (1) Administrative rank upgrade significantly enhances regional innovation with long-term positive effects; (2) Spatial spillover effects follow an inverted U-shape, peaking at 60 km and remaining significant within 30–120 km; (3) Population agglomeration and economic agglomeration are key mechanisms, with economic agglomeration having greater impact.DiscussionThis study provides theoretical insights for optimizing administrative resource allocation, advancing institutional reform, and refining national innovation-driven development strategies.